Development of Digital Information Systems for Operational Efficiency of Savings and Loan Cooperatives - Heru Saputra; Ilfa Stephane; Nency Extise Putri; Elisa Daniati Edison; Gusrino Yanto (Komunitas Dosen Indonesia, 2025)
Savings and loan cooperatives are essential for advancing financial inclusion, especially in rural communities. However, many cooperatives still rely on manual or semi digital systems such as spreadsheets to manage member data and financial transactions. This condition results in low efficiency, delayed reporting, limited transparency, and frequent recording errors. This study aims to design and implement a web based cooperative information system to address operational inefficiencies at Korong Gadang Cooperative in West Sumatra, Indonesia, which serves over 120 active members. The system was developed using the Rapid Application Development (RAD) method, which emphasizes iterative prototyping and user involvement to accelerate development. The process consisted of three stages: requirements planning, system design and construction, and implementation. Modules include member management, savings and loan transactions, financial reporting, and an interactive dashboard. Black Box Testing was used to validate functionality, and user feedback was collected from 12 cooperative staff through questionnaires. The results show significant improvements in performance. Report preparation time decreased from 3–5 days to just 1 day. The system also enhanced data accuracy and transparency, enabling members and staff to access transaction information in real time. In conclusion, the web based cooperative information system developed with the RAD method has proven effective in improving efficiency and accountability. The system can be adopted by similar small-scale cooperatives with basic digital infrastructure. Future development may include mobile access, integration with payment systems, and analytical features to support data driven decisions.